ANALYSIS OF THE FOUL LANGUAGE OF ADOLESCENTS FROM WHATSAPP GROUPS IN BONISARI VILLAGE, PAKUHAJI DISTRICT, TANGERANG REGENCY - Abdul Malik; Goziyah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
In the youth association, they will definitely create a whatsapp group. The Whatsapp application makes it easier for teenagers to interact. Much of the content of the chat contained inappropriate remarks, one of which was abusive language. Teenagers who see the content of the chat, of course, cannot consider whether the speech is appropriate if it is said in public. Many of them imitate the harsh language of the chat on the Whatsapp application. The focus of this research is to find out what types of foul language they type from messages in Whatsapp groups. This type of research is qualitative, with the subject of a group of adolescents in Bonisari Village, Pakuhaji District, Tangerang Regency, From the results of the research, many types of coarse language were found that they spoke. This type of coarse language can be classified into three types, namely conditions, animal names, astral beings, an object, and parts of human body organs. They confess that, from their Whatsapp group messages.